ANALISIS PEMANFAATAN MEDIA YOUTUBE DALAM PEMBELAJARAN DARING DIMASA PANDEMI COVID-19 PADA SISWA KELAS III SEKOLAH DASAR - Nadiah Syaidah; Nur Azmi Alwi; Diren Agasi (Cerdas Proklamator, 2022)
This study aims to describe the use of Youtube media in online learning during the COVID-19 pandemic in third grade students of SD Negeri 25 Pegambiran, Padang City. In the teaching and learning process, especially in online learning, various types of media can be used, one of which is Youtube. Youtube is an application that is a place for various videos that can be accessed and uploaded and downloaded by users using network access. The use of Youtube media is expected that students will be interested and understand the material being taught well. This study also aims to find out the obstacles that occur in the use of Youtube in online learning in third grade students of SD Negeri 25 Pegambiran, Padang City. This research method is a qualitative description with a descriptive type with the research subject of class III teachers. Research data obtained in three ways, namely observation, interviews and documentation. Data were analyzed by collecting data, sorting data, displaying data and then drawing conclusions. This research was conducted in the third grade of SD Negeri 25 Pegambiran, Padang City. The results showed that the features used by teachers from the Youtube application were video descriptions, Thumbnail adjustments, playlists, schedules, Share Links, and end screens. The steps taken by the teacher in utilizing Youtube in online learning consist of two stages, namely the preparation stage and the implementation stage. Constraints faced when using Youtube in online learning systems are (1) Internet quota (2) Unable to interact online. The solution is (1) Opening the link directly without moving to Youtube (2) Using the comments and Live Streaming features. Keywords: Utilization of Youtube Media, Online Learning.